Analisis Tindak Tutur Komisif Capres Pada Debat Ke Lima Pemilu 2024 - Rima Putri Khasanah; Nabila Putri Kinanti; Reindani Rahayu Saputri; Rizka Septiana Puteri; Karina Karina; Asep Purwo Yudi Utomo; Nurnaningsih Nurnaningsih (Student Research Journal, 2024)
Elections are crucial moments in the life of a country’s democracy. The 2024 elections in Indonesia are receiving a spotlight on the increasing intensity of the debate between presidential candidates (presidential candidates). Political debate is incumbent on candidates to present their ideas and vision to voters. Therefore, the commission’s action analysis of the debates is relevant to the study. The purpose of this study is to analyze the actions of the commissar by the presidential candidate in the 2024 fifth-election debate. The method used is a wacky analysis with a qualitative descriptive approach. The data was qualitatively analyzed using a transcript of the debate video. Research has shown that the commission’s speech in the 2024 election debate video includes the commission’s pledge, intent, and vows. The study found that the dominant act of the commissioner’s speech, that of the commission’s actions and the commission’s actions, was committed. Recruiters use appointments to appeal to voters by offering solutions to issues faced by society. Moreover, the action of the promised intention is also a major focus in persuading voters. The benefit of the study was to provide a deeper understanding of the commission communication strategies used by the presidential candidates in political debates. The results of the analysis can be a reference to voters to understand the messages delivered by the presidential candidate and their implications in the presidential election. Additionally, it can also provide the basis for further research in pragmatic politics and political communication.